2020
DOI: 10.1590/0102-4698210405
|View full text |Cite
|
Sign up to set email alerts
|

Teorias Da Aprendizagem Em Publicações Na Área De Educação Em Engenharia: Um Mapeamento Com Foco Na Disciplina De Cálculo I

Abstract: RESUMO: O objetivo principal desta pesquisa foi identificar quais teorias da aprendizagem fundamentam a ação docente e são referenciadas em trabalhos voltados para a disciplina de Cálculo I. Para tanto, foi realizado um levantamento a partir da produção acadêmica brasileira divulgada no Congresso Brasileiro de Educação em Engenharia no período 2010-2017. Sendo assim, por meio de uma pesquisa bibliográfica de caráter qualitativo, 23 trabalhos foram eleitos para constituir o portfólio final desta investigação. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The study revealed a very limited collection of articles, scarcely explored by the academic community compared to other themes approached at the congress. Alzahrani et al (2021) showed that the number of published articles that linked current themes on quality (Quality 4.0-involving all concepts of Industry 4.0 Quality Management) with learning approaches in HEIs is inferior to the collection compiled by Zarpelon and Resende (2020), even when considering five global article databases (Google Scholar, Web of Science, Scopus, Ebsco, and ProQuest). This highlights that the number of works that bring practical approaches to teaching methods is even narrowed, oftentimes limiting itself to the replicability of approaches that involve games for executing practical instruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed a very limited collection of articles, scarcely explored by the academic community compared to other themes approached at the congress. Alzahrani et al (2021) showed that the number of published articles that linked current themes on quality (Quality 4.0-involving all concepts of Industry 4.0 Quality Management) with learning approaches in HEIs is inferior to the collection compiled by Zarpelon and Resende (2020), even when considering five global article databases (Google Scholar, Web of Science, Scopus, Ebsco, and ProQuest). This highlights that the number of works that bring practical approaches to teaching methods is even narrowed, oftentimes limiting itself to the replicability of approaches that involve games for executing practical instruction.…”
Section: Introductionmentioning
confidence: 99%
“…The research scenario regarding teaching methods with practical approaches in higher education institutions is poorly explored by academic initiatives of research according to Alzahrani et al (2021) and Zarpelon and Resende (2020). Zarpelon and Resende (2020) carried out, at the Brazilian Congress of Engineering Education, throughout the 2010-2017 period, a survey of all publications related to the application of learning theories in the teaching of engineering, focusing on the Calculus 1 subject. The study revealed a very limited collection of articles, scarcely explored by the academic community compared to other themes approached at the congress.…”
Section: Introductionmentioning
confidence: 99%